2022
DOI: 10.1039/d1nj05644a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-styryl-quinazoline and 3-styryl-quinoxaline based sulfonate esters via sp3 C–H activation and their evaluation for α-glucosidase inhibition

Abstract: Synthesis of 2-styryl-quinazolines and 3-styryl-quinoxaline based sulfonates is reported via sp3 C-H functionalization in the presence of triethylamine (10 mol%). The resulting compounds were tested for the α-glucosidase enzyme inhibition...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…For example, Missioui et al, reported that the N ‐acetamide quinoxaline derivative Q1 exhibited remarkable antidiabetic activity with inhibitory activity IC 50 values of 199.7 ± 0.952 and 83.78 ± 0.888 µM compared with acarbose (IC 50 = 115.6 ± 0.574 and 72.58 ± 0.682 µM) against α‐amylase and α‐glucosidase enzymes, respectively (Missioui et al, 2021). Moreover, Satyanarayana et al, synthesized 3‐styryl‐quinoxalines with sulfonate group and explained that the presence of substituent at the para position in sulfonate moiety affected the inhibitory activity, such as quinoxaline derivative Q2 that revealed α‐glucosidase activity with IC 50 = 32 ± 2.11 µM compared with acarbose IC 50 = 33 ± 2.65 µM (Satyanarayana et al, 2022). Settipalli et al, synthesized a series of quinoxaline hybrids with 1,2,3‐triazole‐methylene derivatives Q3 and Q4 and exhibited potent inhibitory percentages (IP) ranging from 68% to 73% compared with acarbose (IP = 86%) at 100 µg/mL and the higher activity attributed to 4‐tolyl and morpholinyl rather than pyrrolidine or piperidine (Settypalli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Missioui et al, reported that the N ‐acetamide quinoxaline derivative Q1 exhibited remarkable antidiabetic activity with inhibitory activity IC 50 values of 199.7 ± 0.952 and 83.78 ± 0.888 µM compared with acarbose (IC 50 = 115.6 ± 0.574 and 72.58 ± 0.682 µM) against α‐amylase and α‐glucosidase enzymes, respectively (Missioui et al, 2021). Moreover, Satyanarayana et al, synthesized 3‐styryl‐quinoxalines with sulfonate group and explained that the presence of substituent at the para position in sulfonate moiety affected the inhibitory activity, such as quinoxaline derivative Q2 that revealed α‐glucosidase activity with IC 50 = 32 ± 2.11 µM compared with acarbose IC 50 = 33 ± 2.65 µM (Satyanarayana et al, 2022). Settipalli et al, synthesized a series of quinoxaline hybrids with 1,2,3‐triazole‐methylene derivatives Q3 and Q4 and exhibited potent inhibitory percentages (IP) ranging from 68% to 73% compared with acarbose (IP = 86%) at 100 µg/mL and the higher activity attributed to 4‐tolyl and morpholinyl rather than pyrrolidine or piperidine (Settypalli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, substantial efforts have been devoted to construct quinoxalines leading to the development of a wide spectrum of methods usually employing either condensation [12] or multicomponent [13] reactions. Besides, a number of methods have also been reported for 2‐styryl quinoxalines [9c,14] using substrates like 2‐methylquinoxaline whose methyl group reacts either with aldehydes in presence of acid [9c] /base [14a] or with alcohols [14b] in the presence of a nickel(II) catalyst. A recent trend is to attempt to direct the coupling of quinoxalines with vinyl derivatives through Heck reactions [15a] or C−H activation by using a metal catalyst [15b] .…”
Section: Introductionmentioning
confidence: 99%